Liquidity in Asset Pricing: Evidence from the Brazil Market - Yang, Yuanyu (2012)
This study investigates the role of liquidity in pricing stock returns in the Brazil stock market using a sample of listed stocks in Brazil market from January 2001 to December 2011. The key finding of this study is that liquidity is an important factor for pricing returns in Brazil market even after controlling for size and book-to-market and the liquidity effect is not restricted to the month of January alone. The results are also not influenced by the financial crisis.